2020
DOI: 10.1021/acsanm.0c01457
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Nucleic Acid Biosensing Using Nanomaterial-Based Localized Surface Plasmon Resonance Imaging: A Review

Abstract: In the past couple of decades, the development of plasmonic nanosensors underwent rapid progress in the fields of fabrication, integration, and realized applications. Localized surface plasmon resonance imaging (LSPRi) promises the possibility of high-throughput biomolecule sensing integrated into miniaturized point-of-care devices. This paper aims to provide a critical review of the LSPRi-compatible sensor nanofabrication technologies and compare the most crucial characteristics of implemented LSPRi sensors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 143 publications
0
27
0
Order By: Relevance
“…Changes either in the bulk refractive index of the surrounding liquid or gas or in molecular events such as bioreceptor–analyte binding on the surface of the nanoparticles cause a detectable redshift in their light extinction spectrum [ 3 ]. Several excellent review papers can be found that demonstrate how to utilize this effect in a large variety of sensing applications [ 4 ], from gas sensing [ 5 ] to chemical and biosensing [ 6 , 7 ], e.g., for biomarker [ 8 , 9 , 10 ] or nucleic acid detection [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes either in the bulk refractive index of the surrounding liquid or gas or in molecular events such as bioreceptor–analyte binding on the surface of the nanoparticles cause a detectable redshift in their light extinction spectrum [ 3 ]. Several excellent review papers can be found that demonstrate how to utilize this effect in a large variety of sensing applications [ 4 ], from gas sensing [ 5 ] to chemical and biosensing [ 6 , 7 ], e.g., for biomarker [ 8 , 9 , 10 ] or nucleic acid detection [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…SPR, characterized by its label-free biomolecular quantification, is promising for POC nucleic acid testing through combination with microfluidic chip coated with plasmonic nanomaterials, exhibiting favorable features of excellent sensitivity and real-time information output ( Bonyár 2020 ). The detection principle is based on monitoring the refractive index change on the chip surface.…”
Section: Sample-in-quantitative-answer-outmentioning
confidence: 99%
“…[38] When multiple nanoscale structures are combined together into an array, unique plasmonic capabilities can also be obtained as evidenced in nanoarray and nanolattice plasmonic biosensors, including nanohole and nanoslit arrays, nanodisks, and nanoparticle functionalized surfaces. [40][41][42] Other notable examples of nanoarray structures were outlined in a recent review by Jiang et al [40] These include nanocrescents, [43][44][45] nanocross and bar, [46,47] and nanobowls. [48][49][50] Another relatively common phenomena utilized in optical biosensing is SERS.…”
Section: Optical Biosensorsmentioning
confidence: 99%